Energy efficiency in sustainable buildings: a systematic review with taxonomy, challenges, motivations, methodological aspects, recommendations, and pathways for future research - Fatma S. Hafez; Bahaaeddin Sa’di; M. Safa-Gamal; Yap, Taufiq Yun Hin; Moath Alrifaey; Mehdi Seyedmahmoudian; Alex Stojcevski; Ben Horan; Saad Mekhilef (Elsevier Ltd., 2022)
In recent years, increasing interest has been shown in targeting energy efficiency as a roadmap for carbon mitigation, limiting energy use, improving buildings’ energy performance, and reducing energy consumption for achieving sustainable buildings. This article presents a systematic review to provide the best practices in this area and identify the challenges, motivations, recommendations, and pathways for future work. Discussing the methodological aspects gives insights for future researchers. This research used papers published on three scientific and reliable databases—Web of Science, ScienceDirect, and IEEE Xplore-from 2014 to May 23, 2021. The selected papers reached N = 134 based on inclusion and exclusion criteria and divided into review papers, proceeding conference, and articles. The review articles (N = 16/134) give an overall view on improving energy efficiency to achieve sustainability in buildings by using green building rating systems, developing and implementing policies, technology utilization, adopting techniques, and applying strategies. The conferences (N = 33/134) and articles (N = 85/134) focus more on details of different aspects of improving energy efficiency by reducing environmental, economic, social, and other impacts. A few articles proposed multiple-criteria decision-making methods to solve energy efficiency gaps for promoting sustainability in buildings. Achieving energy efficiency toward sustainable buildings is a hot topic in the sustainable development area. The outcomes from this paper will provide a valuable reference to stakeholders, governments, and decision-makers and give suggestions from the selected past studies. This review will provide motivation and attract future research endeavors in the field.